`In Situ Hybridization for Detection of Latent Epstein-Barr Virus Early Repeats(EBERS) and Mutant-P53- Tumor Suppressor Gene in Patients with Non- Hodgkins Lymphoma - Mohammed Ali, Saad H.; Hammodi, Salim R.; Abdul Amir, Amir H. (Journal of the Faculty of Medicine Baghdad, 2013)
Back ground: Epstein- Barr virus (EBV) is a ubiquitous in that infecting more than 90% of adult population worldwide. Recently, EBV has been linked to the development of variety of human malignancies. P53 gene is mutated in more than 50% of human cancers. Cell cycle dysregulation, measured by p53 protein expression, and latent EBV infection are important in the pathogenesis of Non-Hodgkin’s lymphomas. Objective: To analyze the distribution and impact of concordant p53 expression and latent EBV infection on a group of B & T cell types of NHL. Materials and Methods: Forty (40) formalin-fixed, paraffin embedded tissue blocks were obtained from lymph nodes biopsies related to patients with NHL. In addition, biopsies of twenty (20) lymph nodes autopsies were included as apparently normal control group. The clinico- pathological criteria of NHL cases were assessed and In Situ Hybridization( ISH ) techniques for mutant p53 and Epstein-Barr Early Repeats(EBERs) detection were performed. Results: The percentage of EBV-ISH reaction results in the total group of NHL was (60%), where its percentage in NHL, B-cell type was (58.6%)and in NHL, T-cell type (63.7%). None of the control group showed EBV-ISH reaction. Statistical analysis showed significant difference between these groups (p<0.05). The percentage of B-cell lymphoma with moderate signal score for EBV-ISH test was (41.4%) while with strong scoring was (17.2%). In the T-cell lymphoma, moderate signal scoring was (18.2%) while strong scoring was(45.5%). Statistically, they showed no significant differences (p> 0.05). Mutant p53 gene was observed in 60% of NHLs and dual positivity of EBV and p53-ISH was found in 42.5 % of cases. Regarding the grades, it was found that the higher level of p53 expression was observed in low grade tumors (39.3% ; 11out of 28) NHL. Conclusion: The present findings indicate that cell cycle dysregulation and EBV-related transformation are important in the pathogenesis of NHL.